Edge Computing From Hype to Reality - Al-Turjman, Fadi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this book, contributors provide insights into the latest developments of Edge Computing/Mobile Edge Computing, specifically in terms of communication protocols and related applications and architectures. The book provides help to Edge service providers, Edge service consumers, and Edge service developers interested in getting the latest knowledge in the area. The book includes relevant Edge Computing topics such as applications; architecture; services; inter-operability; data analytics; deployment and service; resource management; simulation and modeling; and security and privacy. Targeted readers include those from varying disciplines who are interested in designing and deploying Edge Computing. Features the latest research related to Edge Computing, from a variety of perspectives; Tackles Edge Computing in academia and industry, featuring a variety of new and innovative operational ideas; Provides a strong foundation for researchers to advance further in the Edge Computing domain.
Chapter1: The Era of the Personal Cloud: What Does It Mean for Cloud Providers? -- Chapter2: Optimization in Edge Computing and Small-cell Networks -- Chapter3: A comprehensive survey on Architecture for Big Data Processing in Mobile Edge Computing Environments -- Chapter4: Taxonomy of Edge Computing: Challenges, Opportunities and Data Reduction Methods -- Chapter5: Applications of the Internet of Things with the Cloud Computing Technologies- A Review -- Chapter6: Software Defined Internet of Thing to Analyze Big Data in Smart Cities -- Chapter7: Taking Cloud Computing to the Extreme Edge: A Review of Mist Computing for Smart Cities and Industry 4.0 in Africa -- Chapter8: IoT and Edge Computing as a Tool for Bowel Activity Monitoring -- Chapter9: Application of Cloud Computing and Internet of Things to Improve Supply Chain Processes -- Chapter10: A Conceptual framework for Security and Privacy in Edge Computing.
Keywords: Telecommunication; Signal processing; Application software; Communications Engineering, Networks; Signal, Speech and Image Processing; Computer and Information Systems Applications